2017
DOI: 10.7150/oncm.17406
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Remotely Triggered Liposomes to Target Triple Negative Breast Cancer

Abstract: Triple Negative Breast Cancer (TNBC) continues to present a challenge in the clinic, as there is still no approved targeted therapy. TNBC is the worst sub-type of breast cancer in terms of prognosis and exhibits a deficiency in estrogen, progesterone, and human epidermal growth factor 2 (HER2) receptors. One possible option for the treatment of TNBC is chemotherapy. The issue with many chemotherapy drugs is that their effectiveness is diminished due to poor water solubility, and the method of administration di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…One more example of how the use of a targeting agent would ideally improve the selectivity of PDT for the tumor tissue has been shown in a recent study. By using polyethylene glycol-coated, folate conjugated, benzoporphyrin derivative-loaded liposomes for PDT treatment of breast cancer cells, the researchers have reported that these liposomes are targeted for are greater uptake into TNBC cancer cells [136] . Therefore, focusing on the molecular differences of cell death mechanisms induced by PDT, starting with an optimized PS choice and conditions of its delivery and activation, will certainly provide valuable clues for the development of new therapeutic strategies aiming at improving the efficacy of PDT against cancer cells [7,15] .…”
Section: Perspectivesmentioning
confidence: 99%
“…One more example of how the use of a targeting agent would ideally improve the selectivity of PDT for the tumor tissue has been shown in a recent study. By using polyethylene glycol-coated, folate conjugated, benzoporphyrin derivative-loaded liposomes for PDT treatment of breast cancer cells, the researchers have reported that these liposomes are targeted for are greater uptake into TNBC cancer cells [136] . Therefore, focusing on the molecular differences of cell death mechanisms induced by PDT, starting with an optimized PS choice and conditions of its delivery and activation, will certainly provide valuable clues for the development of new therapeutic strategies aiming at improving the efficacy of PDT against cancer cells [7,15] .…”
Section: Perspectivesmentioning
confidence: 99%
“…Other recent publications using PMs as delivery carrier for PDT or for a combined therapy confirmed the high efficiency of this type of nanocarriers (Dehghankelishadi and Dorkoosh 2016, Pellosi et al 2016a, b, 2017. …”
Section: Polymeric Micellesmentioning
confidence: 75%
“…Additionally, their nanometric size (classically 60-120 nm) confer them a high loading capacity of the therapeutic agent. All these properties make this type of systems effective vehicles for the delivery of drugs in PDT (Banerjee 2001, Chen et al 2005, Sneider et al 2017. Certain improvements in liposomal technology and molecular biology have been done, allowing them to have targeting power in order to achieve selective delivery to specific biological targets (Medina et al 2004).…”
Section: Liposomesmentioning
confidence: 99%
“…While extensive work has been conducted with the liposomal CUR formulation, our study focused on aiding the selectivity of CUR by actively targeting the liposomes to the overexpressed receptors on cancer cells. This was achieved by surface modification of liposomes with folic acid which binds to overexpressed folate receptors (FRα) on tumor cells [51][52][53][54][55][56]. FRα, a glycosylphosphatidylinositol (GPI) anchored cell surface protein, belongs to the folate receptor family which uses unidirectional transport of folate into cells [52,56,57].…”
Section: Ivyspringmentioning
confidence: 99%
“…To our knowledge, a direct comparative results showing the difference in curcumin efficiency between non-malignant and cancer cells using folate decorated liposomes has not been demonstrated thus far. To test this comparison in vitro and challenge the selective attribute of curcumin when encapsulated in a targeted liposomal modality, we decided to conduct a parallel study using non-malignant mammary epithelial cells, MCF-12A, and triple negative breast cancer cells (TNBC), MDA-MB-231 [51,[59][60][61][62][63].…”
Section: Ivyspringmentioning
confidence: 99%